The nitrogen value of cover crops: How much N can cover crops replace? - Guillermo S. Marcillo; Resham Thapa; Steven B. Mirsky; Nicolas Martin (Agricultural & Environmental Letters)
Abstract Achieving high corn yields while reducing fertilizer losses seems attainable through nitrogen (N) management decisions that include the use of cover crops (CCs). To determine whether CCs result in a net positive balance between N fertilization and crop utilization, we used US field trial data comparing corn systems with and without CCs, and estimated the amount of N fertilizer that CCs would replace and lead to equivalent grain yields under both systems. Overall, applying lower nitrogen rates to corn without cover crops resulted in similar or higher yields when legumes were used as cover crops (indicating positive nitrogen replacement in the amount of 62 kg ha−1), but lower yields when grasses were used as cover crops (indicating negative nitrogen replacement in the amount of 24 kg ha−1). Our results illustrate the benefits and trade‐offs of integrating single CC species into a corn system, that is, reducing N inputs with legume CCs or supplementing N fertilizer to avoid possible grain yield penalties in the case of grass CCs. Quantifying the N replacement value of CCs would facilitate field‐level recommendations and policy regulations aimed at promoting sustainable corn production in the United States. Core Ideas Managing N fertilizer rates is essential for maximizing the benefits of legume and grass cover crops in corn‐based systems. N fertilizer replacement of grass and legume cover crops was assessed based on data from field experiments in the United States. Legume cover crops were found to positively replace N fertilizer; potentially reducing corn N inputs. Grass cover crops were found to negatively replace N fertilizer; potentially requiring supplementary fertilizer to reduce corn yield penalties.